Perivascular cell αv integrins as a target to treat skeletal muscle fibrosis - Prazeres, Pedro H. D. M. (Int J Biochem Cell Biol, 2018)
Fibrosis following injury leads to aberrant regeneration and incomplete functional recovery of skeletal muscle, but the lack of detailed knowledge about the cellular and molecular mechanisms involved hampers the design of effective treatments. Using state-of-the-art technologies, Murray et al. (2017) found that perivascular PDGFRβ-expressing cells generate fibrotic cells in the skeletal muscle. Strikingly, genetic deletion of αv integrins from perivascular PDGFRβ-expressing cells significantly inhibited skeletal muscle fibrosis without affecting muscle vascularization or regeneration. In addition, the authors showed that a small molecule inhibitor of αv integrins, CWHM 12, attenuates skeletal muscle fibrosis. From a drug-development perspective, this study identifies a new cellular and molecular target to treat skeletal muscle fibrosis.